Deterioro cognitivo en pacientes con VIH/SIDA en el Hospital Isidro Ayora Loja - Ludeña Poma, Santiago Andres (2020)
AIDS is one of the most devastating diseases suffered by humanity. HIV is a neurotropic virus that affects the central nervous system, so many of the infected patients have symptoms of neurological and psychological nature. The objective of this investigation was to identify the relationship between cognitive impairment and treatment of patients with HIV/AIDS in the HIV clinic of the Isidro Ayora Loja hospital according to the degree of cognitive impairment, age and sex; establish the most prevalent treatment received by patients with HIV/AIDS and establish the relationship between the degree of cognitive impairment and treatment. The study was descriptive, cross-sectional, which was performed in 71 patients of the HIV clinic, to whom it was applied the Mini Mental State Examination (MMST). As results we had: 8.45% presented cognitive impairment of which they are in the age group of 26 to 35 years old, the sex where the highest frequency of cases exists is the male sex, the treatment that receives the most frequency patients is the second scheme consisting of: Tenofovir, efavirenz and emtricitabine with 78.87% and the relationship between the degree of cognitive impairment and treatment of patients with HIV/AIDS was obtained that 77.46% do not present cognitive impairment and the treatment they carry is the second scheme with 75%. Conclusions: The age group with the highest number of cases is the one between 26 and 35 years old, the male sex is the most affected by HIV/AIDS, the second scheme is the most used by patients and the largest number of patients with cognitive impairment receive the second scheme. Keywords: HIV/AIDS, cognitive impairment and treatment.